Factors Associated with prolonged Inpatient Stay in Pediatric Patients Admitted for Sever Diabetic Ketoacidosis (DKA) - Samar Mahmoud Abousadegh; Ibrahim ALHelali; Ibrahim AL-Benhassan; Ahmed Al-Hazmi; Dr. Amal Mohammed Alqahtani; Rana Ali Abdullah Shathan; Azzam Hassan Nasser; Sayed Shahbal (Migration Letters, 2023)
Background: Severe Diabetic Ketoacidosis (DKA) is a life-threatening condition in pediatric patients. Understanding the factors associated with prolonged inpatient stay can aid in optimizing management strategies and improving patient outcomes. Aim: This study aimed to identify the factors contributing to prolonged inpatient stay in pediatric patients admitted for severe DKA. Method: A retrospective analysis of 150 pediatric patients admitted for severe DKA was conducted. Demographic variables, clinical features, adherence to treatment, hospitalization rate, length of stay, and clinical outcomes were examined. Statistical analyses, including frequencies and percentages, were performed to analyze the data. Results: The study revealed that age, adherence to treatment, and specific symptoms were significantly associated with prolonged inpatient stay in pediatric patients with severe DKA. Older age groups (9-11 and 12-14 years) had higher rates of prolonged hospitalization. Poor compliance with treatment and specific symptoms such as abdominal pain and vomiting were also found to be associated with longer hospital stays. Conclusion: This study highlights the importance of considering age, adherence to treatment, and specific symptoms in predicting the duration of hospitalization for pediatric patients with severe DKA. These findings emphasize the need for tailored management strategies and interventions to optimize patient care and reduce hospital stay duration. Further research is warranted to validate these findings and explore additional factors that may contribute to prolonged hospitalization in this population.